Design of Multi-function Rehabilitation Wheelchair based on Human-machine Interaction - Pan Lu; Liu Yan; Yang Yan (Jixie chuandong)
In order to solve the problem of single function,poor human-machine interaction of the most wheelchair products on the market. A kind of multi-function wheelchair is designed according to ergonomics principle and interaction design method. The wheelchair could meet the needs of special human with the functions of obstacles crossing,automatic obstacle avoidance,standing deformation,auxiliary rehabilitation treatment. The test results show that the human-machine interaction of the wheelchair is strong compared to the similar products. It can improve the quality of life of the disabled patients.